Pengaruh Bekerja Dari Rumah, Keseimbangan Kehidupan Kerja, Dan Stres Kerja Terhadap Kepuasan Kerja Di Perusahaan Spare Part Manufaktur Otomotif Kabupaten Bekasi Di Saat Pandemi Covid-19 - Widianto, Slamet; Rojuaniah, Rojuaniah (CV. Lafadz Jaya, 2022)
The COVID-19 pandemic, starting in the early 2020s, is changing people's lives and the way they work, and affecting industries and organizations around the world. Many companies or organizations are starting to think about ways to provide security and smoothness to the company's or organization's business in the COVID-19 pandemic situation so that employees are able to carry out their obligations by doing work from home. This study aims to fill the gap by investigating some of the potential predictors of job satisfaction while employees work from home from the impact of the COVID-19 pandemic such as work-life balance and work stress. A quantitative approach is used on 135 employees who work from home in an automotive spare part manufacturing company. The collected data were analyzed using SEM tools. The results revealed that working from home, work-life balance and work stress had a significant effect on job satisfaction. Working from home as a new step in working can sustain job satisfaction as the current working atmosphere for workers. Responding to the situation during the COVID-19 pandemic, working from home can be a positive sign that needs attention for companies or organizations. The results of the study show that there is a strong relationship between working srom home and work life balance and work stress which increases job satisfaction, while work life balance is not positively related to job satisfaction when working from home and working from home during a pandemic can reduce work stress and increase job satisfaction.